Durdānah́hā-yi Turkman-i = zarb al-masalhā-yi Turkman-i - Dūghan, Payghambargul; Dardl-i, Muḥammad Gildī (Parlah pase gaṇah 19., 1983)
Collection of popular Turkemen proverbs with Persian and Pushto translations.